2020
DOI: 10.3390/jof6020051
|View full text |Cite
|
Sign up to set email alerts
|

Silver/Chitosan Nanocomposites: Preparation and Characterization and Their Fungicidal Activity against Dairy Cattle Toxicosis Penicillium expansum

Abstract: This work aimed to evaluate the fungicide activity of chitosan-silver nanocomposites (Ag-Chit-NCs) against Penicillium expansum from feed samples. The physicochemical properties of nanocomposites were characterized by X-ray fluorescence analysis (XRF), small-angle X-ray scattering (SAXS), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM). The morphological integrity of the nanohybrid was confirmed by electron transmission. By the data of RFA (X-ray fluorescent analysis), the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…The genomic DNA fragmentation may be attributed to the physical and chemical properties of the NPs [ 55 ] including the size, concentration [ 56 , 57 ], chemistry [ 56 , 57 , 58 ], and surface functionalization [ 59 ]. Though within a fungal cell the predominant mechanism of degradation of the cellular DNA by ZnNPs is through formation of reactive oxygen species (ROS) which causes extensive DNA scissoring and fragmentation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA fragmentation may be attributed to the physical and chemical properties of the NPs [ 55 ] including the size, concentration [ 56 , 57 ], chemistry [ 56 , 57 , 58 ], and surface functionalization [ 59 ]. Though within a fungal cell the predominant mechanism of degradation of the cellular DNA by ZnNPs is through formation of reactive oxygen species (ROS) which causes extensive DNA scissoring and fragmentation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the treatment of chitosan nanocomposites generates some biological reactions, such as oxidative stress-induced metabolic changes, which in turn affect the protein synthesis rate [ 56 ]. The toxicity of nanocomposites in fungal cells is due to severe metabolic changes, in particular protein synthesis, which resulted in a maximum protein reduction, as verified by the absence of the most important protein synthesis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…When chitosan is applied to a mutation suspension, its titer is reduced with chitosan. Electron microscopic analyses revealed that chitosan induced massive reforms in mutation particles and destabilised their stability (Alghuthaymi et al 2020).…”
Section: Chitosan Utilisation Against Virusesmentioning
confidence: 99%